Use of splenic ultrasound: a new wave for immune thrombocytopenic purpura. Issue 5 (May 1994) - Cervi, P; Murdock, A; Rees, D; Garner, S; Grant, D; Wright, S; Dyson, M
Abstract : AIMS–To examine whether a therapeutic dose of ultrasound waves, when directed through the thoracic wall to the spleen, would significantly affect the platelet count in patients with stable immune thrombocytopenic purpura (ITP). METHODS–Continuous ultrasound at 1 W/cm2 spatial average-time average (SATA) intensity for up to one minute/5 cm2 treatment field was well tolerated in 13 patients with ITP and one with non-Hodgkin's lymphoma. Five healthy controls were also similarly treated. Peak platelet increments occurred four to eight hours after ultrasound treatment in the ITP group (n = 16 treatments). RESULTS–The mean peak platelet increment was 6.25 x 10(9)/l with a 5% confidence interval of the mean (95% CI) of 3.32 to 8.93 x 10(9)/l (p = 0.0004). The mean peak platelet increment of normal controls was 6.6 (n = 5; 95% CI = -2.3 to 15.5; p = 0.21) and for sham treated patients it was 0.66 (n = 11; 95% CI = -1.5 to 2.8; p = 0.60). There was a significant inverse correlation between patient age in the ITP group and peak platelet increment (r = -0.60; p = 0.015). CONCLUSIONS–Splenic ultrasound is a novel approach to the treatment of ITP, and may find a place in its diagnosis or management.